Early nitrogen fixation and utilization in Albizia lebbeck, Leucocephala, and Gliiricidia sepium using nitrogen 15N labeling - Kadiata, B.; Mulongoy, K. (Informa UK Limited, 1995)
High nitrogen (N2)‐fixing potential is a desirable characteristic for any candidate hedgerow tree. Thus a study was conducted to evaluate Albizia lebbeck as a N2‐fixing tree in comparison to Gliricidia sepium and Leucaena leucocephala currently used in alley cropping. Nitrogen fixation and utilization were assessed in a screenhouse at four months after planting by the 15N dilution technique using Senna siamea as the non N2‐fixing reference. A. lebbeck accumulated significantly more N than L. leucocephala, but G. sepium was intermediate. This superiority in N yield was mainly due to its abundant nodule dry weight production which accounted for up to 10.8% of its total N. This was equivalent to 2.5 and 6 fold that of Gliricidia and Leucaena nodules, respectively. A. lebbeck had bigger but significantly (P<0.05) lower number of nodules per plant than G. sepium, but it did not differ from Leucaena. Albizia was the best N2 fixer with 44% Ndfa equivalent to 533 mg N per plant. G. sepium followed with 28% Ndfa and L. leucocephala with 18% Ndfa corresponding to 321 and 191 mg N fixed, respectively. However, the relatively higher N2 fixation in Albizia was not translated into higher N or dry matter yields. As A. lebbeck fixed more N, it depended less on soil N (49.8%) than did Leucaena (72.5% Ndfs) and Gliricidia (63.9% Ndfs) and less on fertilizer N as well. Thus A. lebbeck appears to be a potential hedgerow species for alley cropping purpose.